Efforts to Prevent Obesity in Primary School Children Through Intervention Nutritional Education and Physical Activity – School Based - Rina Oktaria; Meri Neherta; Deswita Deswita (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
One of the problems of excess nutrition that occurs in children and gets special attention in the world of health is obesity. The purpose of this study was to analyze the effectiveness of school-based nutrition education interventions and school-based physical activity in an effort to prevent obesity in school-age children. This research method starts from searching data using five databases, namely Science Direct, Taylor & Francis Online ( Tandfonline ), PubMed, DOAJ and SAGE with a range of 2015-2020 with a total of 2,125 articles. Articles searched for with the keyword "intervention and obesity and physical activity and diet and primary school". It was found that 15 articles met the criteria assessed using the JBI critical appraisal tools. The whole article states that nutrition education and school-based physical activity can affect BMI in school-age children with overweight and obesity. Nutrition education is provided by various methods as well as media. Physical activity is given with the type of fitness intensity, muscle strengthening and bone strengthening. The conclusion from the review of this article is that school-based nutrition education and physical activity interventions are proven to be influential in efforts to prevent obesity in school-age children.